Investigating the Performance of Papyrus Ash in Concrete to Reduce Defects Caused Due to Carbonation - Philip Ajutu (Uganda Christian University, 2024)
Reinforced concrete structures are susceptible to a process called carbonation. This occurs when carbon dioxide from the atmosphere reacts with the calcium hydroxide in the concrete, gradually lowering its pH and compromising the protective oxide layer around the steel reinforcement. The papyrus ash used in this study was collected from buzilanjovu wetland in Mukoko. The Physical and mechanical properties of concrete ingredient such sand and coarse aggregates were determined and these included sieve analysis, ACV, AIV, moisture content, flakiness index, specific gravity and porosity. The control mix of a cement content of 400 kg, aggregate cement ratio of 4.15, 7% of the aggregate of the aggregate was used as fine aggregate, and a water cement ratio of 0.5 was used. The percentage replacement of fine aggregates with papyrus ash varied from 0, 2, 4, 6, 8, and 10 %. Concrete cubes of sizes 150 mm x 150 mm x 150 mm were casted and evaluated at 7 and 28 days. Increasing the replacement of fine aggregates with papyrus ash improved compressive strength but also increased porosity in hardened concrete. Despite this, compressive strength, porosity, and permeability remained within acceptable ranges (35.9 MPa, 17%, 0.34 cm/s respectively). The optimal replacement was 10%, meeting all criteria and design strength (35.9 MPa). Future research should aim to enhance workability, strength properties, and expand the material's applicability to higher concrete classes.